BIOCHEMICAL CHARACTERIZATION OF EFFICIENT TRICHODERMA SPECIES IN ASSOCIATION TO THEIR TOLERANCE EFFICACY TO FUNGICIDES - PRATIK JAISAN,; R.N. PANDEY,; D. L. YADAV, (The Bioscan, 2021)
Development of tolerance in efficient Trichoderma spp. isolates against fungicides as a part of the biocontrol strategy in plant disease management aimed to make biocontrol agent more effective in suppressing phytopathogens. Eight isolates belonging to Trichoderma harzianum, T. viride, T. virens and T. asperellum collected from rhizospheric soils of tomato, brinjal, sorghum, tobacco and groundnut were morphologically characterized revealing significant differences in terms of colony characters; sporulation; mycelial form; branching of conidiophores; phialospores color and shape. In vitro studies on effect of fungicides on radial growth of as well as tolerance induction in T. viride, T. harzianum, T. virens and T. asperellum subjected to increasing gradient of fungicides showed that the bioagents acquired tolerance to the higher doses of fungicides viz. Metalaxyl, Thiram, Mancozeb, Chlorothalonil, Copper oxychloride. While evaluating the ED50 values for fungicides, it indicated T. viride, T. harzianum, T. virens and T. asperellum could tolerate maximum to Metalaxyl followed by Metiram, Mancozeb, Thiram and Copper oxychloride even at higher concentration and not to Hexaconazole, Carbendazim, Propiconazole and Carbendazim (12%) + Mancozeb (63%). Protein profile of T. viride, T. harzianum, T. virens and T. asperellum isolates tolerant to higher concentration of fungicides analysed through SDS-PAGE indicated the increase in the protein content in form of more number of protein bands of higher molecular weight as compared to non- tolerant isolates.